2004
DOI: 10.1074/jbc.m310292200
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Quinones with Thioredoxin Reductase

Abstract: Mammalian thioredoxin reductases (TrxR) are important selenium-dependent antioxidant enzymes. Quinones, a wide group of natural substances, human drugs, and environmental pollutants may act either as TrxR substrates or inhibitors. Here we systematically analyzed the interactions of TrxR with different classes of quinone compounds. We found that TrxR catalyzed mixed single-and two-electron reduction of quinones, involving both the selenium-containing motif and a second redox center, presumably FAD. Compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
87
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(102 citation statements)
references
References 49 publications
14
87
1
Order By: Relevance
“…The Cys-59 thiolateand charge-transfer-containing active site is thereby instead available for other types of reactions, including one-(or two-) electron reduction of quinones such as juglone. This line of reasoning is supported by the known high capacity of native, Sec-derivatized as well as Sec-lacking truncated forms of TrxR in reduction of juglone directly through the N-terminal redox active motif (38,39,68). Hence, without resonance effects of Tyr-116 and therefore a lack of an efficient reductive half-reaction, the result would easily be the observed increased propensity for juglone reduction but diminished activity with Trx as substrate.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The Cys-59 thiolateand charge-transfer-containing active site is thereby instead available for other types of reactions, including one-(or two-) electron reduction of quinones such as juglone. This line of reasoning is supported by the known high capacity of native, Sec-derivatized as well as Sec-lacking truncated forms of TrxR in reduction of juglone directly through the N-terminal redox active motif (38,39,68). Hence, without resonance effects of Tyr-116 and therefore a lack of an efficient reductive half-reaction, the result would easily be the observed increased propensity for juglone reduction but diminished activity with Trx as substrate.…”
Section: Discussionmentioning
confidence: 96%
“…However, considering that juglone can be efficiently reduced by either the C-terminal selenolthiol motif or directly by the N-terminal FAD/dithiol motif of TrxR (38,39,68) and considering the plausible roles of Tyr-116 in the reductive and oxidative half-reactions, as described above, the effects of Tyr-116 mutations become explainable. Hence, we propose that the Tyr-116 substitutions diminish the possibility for the Cys-59 thiolate to attack Sec-498 of the selenenylsulfide, thereby mainly leaving the selenenylsulfide in the inactive oxidized state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The catalytic mechanism of mammalian TrxR is well understood (5). However, less is known about endogenous cellular factors that modulate its activity.…”
mentioning
confidence: 99%
“…A possible mechanism for o-quinone reduction is the thioredoxin reductase/thioredoxin (TR/ T) system. 3) In human keratinocytes and melanocytes, the presence of the TR isoform has been demonstrated, 4) while 6BH 4 can reduce o-quinone L-dopaquinone back to L-dopa. 5) It has been found that keratinocytes and melanocytes have a capacity for de novo synthesis, recycling, and regulation of 6-tetrahydrobiopterin (6BH 4 ).…”
Section: Effects Of Tetrahydropterines On the Generation Of Quinones mentioning
confidence: 99%